Factor influence pre-marital pregnancy in Yogyakarta, Indonesia: a qualitative study - Endang Koni Suryaningsih; Meei Ling Gau (Universitas Aisyiyah Yogyakarta, 2021)
Getting pregnant before married will raise the multifaceted consequence that can affect to the maternal mental health. In Indonesia, the incident stigmatized as the negative event and particularly, female, will have insecure feeling in their own family as well as in the community. However, the studies have been recognized the predictors of getting pregnant before married among adult. This study aimed to explore the predictors of unwanted pregnancy among Indonesian adults. Qualitative approach has been established and in-depth interview has been applied.The researcher invited teenager who eligible such as female, aged under 18, and they got pregnant before married in Bantul Regency. The main resource of data was based on the local Civil Registry Office, and the secondary data based on headman of targeted districts. Sample sized is determined using snowball sampling. The researcher has assisted by health cadres for each districts for facilitating the process of data collection. To test the validity, triangulation has been used. The parents and partner of participants have participated in this study. The observation during interaction with participants also has been done to support the validity of the result. The researcher have found in relationship, lack of knowledge, and social, as well as lack of awareness from parents are the main factors influence to getting pregnant before married among teenager in Yogyakarta, Indonesia.The findings is important for parents to build positive communication with their adolescence children. The local Civil Registry Office need to consider to collaborate with health care provider to provide information on the consequence of pregnancy before married through the program of local Civil Registry Office goes to school. Nurse and midwives need to advocate an unexpected women to have access of health.